Resistências semiáridas: sobre a produção e circulação de conhecimentos pela rede sociotécnica do milho, estiagem e os indígenas Xakriabá do norte de Minas Gerais - Rebeca Cássia Andrade (2019)
Xakriabá indigenous people of Minas Gerais Brazil live in lands located in the north of these state, with characteristic features of a semi-arid savanna environment. The production of food in Xakriaba fields, where maize has a leading role, generates not only food, but knowledge; practices; close relationships with environment, with other people, with beings; makes relatives; and relates to the resistance of this people. In this thesis, such relations are understood in an actor-network, when both human and nonhuman actions produce the local reality. To do this, by taking maize as an agent of entry into this reality network, the actions of other entities, human or otherwise, were symmetrically observed, described and analyzed as a way of recognizing the ways in which maize, drought and the Xakriabá interact in production and circulation of knowledge and science. The relationships between humans and nonhumans in the described actor-network suggest the existence of the hybrid maize-Xakriaba and demonstrate that plantations, foods and kitchens can together with the Xakriaba natives produce masters of the tradition of memory and courage. It is considered that the relations between Xakriaba-drought-maize produce and circulate different knowledge about times, spaces, presences and diverse sensitive dimensions of the semi-arid north of Minas Gerais. Important questions that can be worked out in different education practices considering their multiple realities are whether they are indigenous, rural or urban.